2018
DOI: 10.1111/obr.12764
|View full text |Cite
|
Sign up to set email alerts
|

‘The rollercoaster of follow‐up care’ after bariatric surgery: a rapid review and qualitative synthesis

Abstract: Summary Benefits of bariatric surgery for obesity related comorbidities are well established. However, in the longer term, patients can become vulnerable to procedure specific problems, experience weight regain and continue to need monitoring and management of comorbidities. Effective longer term follow‐up is vital due to these complex needs post‐surgery. Current guidance recommends annual long‐term follow‐up after bariatric surgery. However, attendance can be low, and failure to attend is associated with poor… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

7
93
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 48 publications
(100 citation statements)
references
References 63 publications
(319 reference statements)
7
93
0
Order By: Relevance
“…Some show certain aspects of HRQL to improve but not others 11 12 18. Previous qualitative research has highlighted the complex and changeable nature of the psychosocial impact of bariatric surgery, helping to shed light on some of these inconsistencies in the HRQL literature and emphasising the importance of long-term postoperative support in helping patients manage these changes 10 19. Previous research has also reported attendance at follow-up visits to be associated with better weight loss outcomes after bariatric surgery 20.…”
Section: Introductionmentioning
confidence: 99%
See 3 more Smart Citations
“…Some show certain aspects of HRQL to improve but not others 11 12 18. Previous qualitative research has highlighted the complex and changeable nature of the psychosocial impact of bariatric surgery, helping to shed light on some of these inconsistencies in the HRQL literature and emphasising the importance of long-term postoperative support in helping patients manage these changes 10 19. Previous research has also reported attendance at follow-up visits to be associated with better weight loss outcomes after bariatric surgery 20.…”
Section: Introductionmentioning
confidence: 99%
“…Qualitative research is useful to explore patients’ perspectives as it seeks to gain the insider’s view on how people view, experience and make sense of their social world 25–27. The primary focus of most previous qualitative research in bariatric surgery has been on patient experiences of outcomes of surgery rather than experiences of follow-up care 10 19. Studies that have reported on aspects of care have identified patient need for longer follow-up after bariatric surgery, better access to psychological support and the ability to communicate with health professionals between routine appointments 19 28–36.…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…A recent UK study synthesised the available published literature on patient experiences on clinician follow-up from 12 months after bariatric surgery. 3 They found a clear need for improved nutritional and psychological support. Patients were more likely to engage if clinicians had nonjudgemental attitudes, were knowledgeable, and were able to offer continuity of care.…”
Section: Traumatic Brain Injury Lung Cancer Bariatric Surgery and mentioning
confidence: 99%